Becoming Sustainable, Underground : Outdoor Parties Resisting Cultural Extractivism in the Pandemic Summer of 2020 - Bottà, Giacomo (Equinox publishing, 2023)
In the pandemic summer of 2020 in Helsinki, UG outdoor parties were able to disengage electronic live music practices from profit making and the logics of cultural extractivism, offering a sustainable practice by and for the local techno music scene. In this article, the UG parties are understood as a learning experience, in which sustainability gave access to a different way to produce and consume culture, in particular thanks to: (1) safe space and pedagogy, (2) ecological awareness, (3) non-profit and community building, (4) music curating, and (5) randomness and exploration. The UG party scene moved outdoors, with no profit to be made, and mostly on public land located in wastelands, shorelines, and forests. This operation suspended cultural extractivism through means that had been previously developed, but that acquired a new dimension because of being performed outdoors. The physical borders of indoor private spaces, and their real estate dimension, is the key issue in relation to music extraction. When played in public natural settings, with no clear borders or limitations, music is able to regain a political dimension. The mixed-methods approach I used here involves interviews, digital ethnographies and post-party on site explorations and was based on a thoughtful reflection on how to overcome ethical research issues on one side, and the fear of contagion on the other. A scene as a local actor in times of crisis plays a significant role in keeping social practices alive, and in defining ways to overcome and learn from difficult times.
Keywords: pandemiat; musiikki; COVID-19; kulttuuri; tekno; kaupunkikulttuuri; kestävä kehitys; Helsinki